2015
DOI: 10.1371/journal.pone.0139112
|View full text |Cite
|
Sign up to set email alerts
|

CD24 Overexpression Is Associated with Poor Prognosis in Luminal A and Triple-Negative Breast Cancer

Abstract: CD24 is associated with unfavourable prognoses in various cancers, but the prevalence of CD24 expression and its influence on clinical outcome in subtypes of breast cancers remain unclear. CD24 expression was analyzed by immunohistochemistry in 747 breast cancer tissues, and DNA methylation and histone modification status in the promoter region of CD24 were assessed using bisulfite sequencing and chromatin immunoprecipitation assay. 213 (28.5%) samples exhibited high CD24 expression in the membrane and/or cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(62 citation statements)
references
References 36 publications
2
57
3
Order By: Relevance
“…However, due to the lack of data, it is difficult to definitely say that a difference in side-effect profile between palonosetron and ramosetron does not exist. None of the studies included in the present meta-analysis reported any severe cardiac adverse events, such as QT prolongation or fatal arrhythmias, which corresponds to the results of previous studies that reported the safety of palonosetron and ramosteron on the QT interval 30313233…”
Section: Discussionsupporting
confidence: 83%
“…However, due to the lack of data, it is difficult to definitely say that a difference in side-effect profile between palonosetron and ramosetron does not exist. None of the studies included in the present meta-analysis reported any severe cardiac adverse events, such as QT prolongation or fatal arrhythmias, which corresponds to the results of previous studies that reported the safety of palonosetron and ramosteron on the QT interval 30313233…”
Section: Discussionsupporting
confidence: 83%
“…[10][11][12] Elevated CD24 expression has been observed on many types of cancer cells, including breast, ovary, bladder, prostate, and uterine cervical cancer, and is associated with tumor growth and progression. [13][14][15][16][17][18] In the present study, we sought to gain more insight into the role of CD24 in oral cancer. In contrast to other cancers, we found that higher CD24 expression level in the tumor microenvironment confers better survival in oral cancer patients.…”
Section: Introductionmentioning
confidence: 99%
“…But when observing changes in histone acetylation there have been multiple findings recently that point to this having an effect as well. Kwon and colleagues discovered a correlation between histone acetylation and CD24, which leads to an unfavorable prognosis in TNBC through hypoacetylation [40]. Although these are only a few genes responsible for TNBC this paints a picture on what role methylation and acetylation play in altering TNBC probability.…”
Section: Genetic Subtyping Of Tnbcmentioning
confidence: 99%